Diuretic therapy in congestive heart failure. Issue 2 (7th February 2022) - Kennelly, Patrick; Sapkota, Rajju; Azhar, Maimoona; Cheema, Faisal Habib; Conway, Claire; Hameed, Aamir
Abstract: In heart failure, fluid overload is a major pathological mechanism leading to vascular congestion, pulmonary congestion and elevated jugular venous pressures. Diuretics play a significant role in the management of patients with congestive heart failure. It is used to relieve the congestive symptoms of heart failure. However, the appropriate use of diuretics remains challenging due to various complications like electrolyte abnormalities, worsening renal function and diuretic resistance. This has prompted towards the search of safer and effective alternatives. This review evaluates the use of diuretics in congestive heart failure and discusses the complications of different types of diuretics, which is essential for successful management of congestion in patients with heart failure and hence to optimise the outcome for the patients.